The contribution and challenges of water treatment in achieving the SDGs - Ajam, Wafaa Hufdhy; Al-Gawwam, Zahraa Hamid Mohan; Eidan, Basma Abdel Khaleq; Jebril, Lina Mahmoud Tawfiq; Hamzah, Sarah Hussein; Jebril, Nadia Mahmoud Tawfiq (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In water treatment plants is critical to achieving the adopted sustainable development goals (SDGs) to increase water availability to have goals: SDG 1: no poverty, SDG 2: zero hunger, SDG 3: good health and wellbeing, SDG 4: quality education, SDG 5: gender equality, SDG 6: clean water and sanitation, SDG 7: affordable and clean energy, SDG 8: decent work and economic growth, SDG 9: industry, innovation, and infrastructure, SDG 11: sustainable cities and communities, SDG 12: responsible consumption and production, SDG 13: climate action, SDG 14: life below water, SDG 15: life land, SDG 16: peace,, justice and strong institution and SDG 17: partnerships for the goals. In this review, the possible achieving goals and the challenges that faced the plan anticipated to advance the involvement of the water management competence to the SDGs were outlined. This review highlights the substantial encouragement of water management in the United Nations' SDGs.